Focusing on culture-related episodes in a teletandem interaction between a Brazilian and an American student - Zakir, Maisa A. [UNESP]; Funo, Ludmila B. A. [UNESP]; Telles, Joao A. [UNESP] (Routledge Journals, Taylor & Francis Ltd, 2016)
Teletandem is a telecollaborative learning context that involves pairs of native (or competent) speakers of different languages interacting through voice, text and webcam image. Using Skype, each participant plays the role of learner for half an hour, speaking and practising the language of his/her partner. This paper focuses on a teletandem interaction between a female Brazilian and a male American undergraduate student. We aim to analyse how the participants approach the cultural dimension in a teletandem interaction. In the first part, we present five perspectives on the concept of culture (Levy, 2007. Culture, Culture Learning and New Technologies: Towards a Pedagogical Framework. Language Learning and Technology 11 (2): 104127). We also adopt a new discourse construct presented by Zhu (2012. Weaving Language and Culture Together: the Process of Culture Learning in a Chinese as a Foreign Language Classroom. PhD diss., University of Iowa) from the term coined by Swain and Lapkin (1998. Interaction and Second Language Learning: Two Adolescent French Immersion Students Working Together. Modern Language Journal 82 (3): 320-337), 'language-related episodes' and analyse five 'culture-related episodes'. We define 'culture-related episode' as any segment of a dialogue produced during teletandem sessions in which students focus on any interest, explanation or inquisitiveness about their own or their partner's culture. Our findings provide evidence that the exchanges between people from different nationalities and life experiences engender many possibilities of understanding culture in its various dimensions. Finally, we suggest that further research on learning languages and cultures should be developed to better understand the complexity and the characteristics of online telecollaborative contexts.
Keywords: Teletandem; language learning; cultural learning; culture-related episode